Los estados atributivos y locativos: estudio semántico cognitivo de la caracterización en el español de Lima - Lazo García, Verónica (2021)
Attributive states relate entities of the world to properties. In Spanish, they are expressed, in syntax, as projections of verb phrases structured by copulative or semicopulative verbs, as adjective nuclei and phrases, prepositional phrases, nominal phrases and relative constructions as their complements. At the cognitive level, these semantic-syntactic structures fulfill the same function: the characterization of world objects by a conceptualizer. The aim of this paper is to explain this cognitive process in Spanish by describing its semantic-syntactic structures and their use. For this purpose, a sample of 117 sentences collected through a survey of 31 university students was used. The analysis was carried out according to the postulates of the formal semantics of Moreno Cabrera, 2003; Chafe, 1970; and the cognitive semantics of Talmy, 2000; Fillmore, 1985; and Langacker, 1999. The results of the research show that, from syntax, characterization is most frequently expressed with adjective phrases, and to a lesser degree with prepositional phrases, participles and relative constructions. In terms of usage, attribution is expressed differently in women and men. Thus, women used more attributes to characterize the entities and paid more attention to the conceptual domain of the physical, such as the shape and color of skin and hair, age and attitude. Males, on the other hand, used more eventive characterization and attributions related to the posture of the characterized entity.